2012
DOI: 10.1051/0004-6361/201118486
|View full text |Cite
|
Sign up to set email alerts
|

Space weathering of Vesta and V-type asteroids: new irradiation experiments on HED meteorites

Abstract: Context. In the past few decades, several tens of main belt asteroids have been found to exhibit basaltic surface composition, similar to the one of Vesta and basaltic Howardite, Eucrite, and Diogenite achondrite meteorites (HEDs). Most of these objects (V-types) belong to the Vesta dynamical family. Several questions on the relationship between Vesta, V-types, and HEDs are still unresolved. In particular, Vesta is spectroscopically bluer than most V-types. Aims. To date, it has not yet been understood whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…Currently, laboratory simulations of space weathering can be categorized into three main types: pulsed laser is used to irradiate analog materials to simulate effects of micrometeorite impacts (e.g., Yamada et al 1999;Sasaki et al 2001;Brunetto et al 2006); proton and ion implantations are used to simulate solar-wind irradiations (e.g., Hapke 1973;Yamada et al 1999;Brucato et al 2004;Marchi et al 2005;Fulvio et al 2012;Miller et al 2014;Kuhlman et al 2015); and thermal treatment is also used to simulate the production of npFe 0 (e.g., Tang et al 2012). Recently, Kohout et al (2014) developed a double heating method to produce npFe 0 in a controlled way.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, laboratory simulations of space weathering can be categorized into three main types: pulsed laser is used to irradiate analog materials to simulate effects of micrometeorite impacts (e.g., Yamada et al 1999;Sasaki et al 2001;Brunetto et al 2006); proton and ion implantations are used to simulate solar-wind irradiations (e.g., Hapke 1973;Yamada et al 1999;Brucato et al 2004;Marchi et al 2005;Fulvio et al 2012;Miller et al 2014;Kuhlman et al 2015); and thermal treatment is also used to simulate the production of npFe 0 (e.g., Tang et al 2012). Recently, Kohout et al (2014) developed a double heating method to produce npFe 0 in a controlled way.…”
Section: Introductionmentioning
confidence: 99%
“…After irradiation samples have been removed from the vacuum chamber and further spectral analysis has been obtained ex-situ in a wider spectral range (see e.g., Strazzulla et al, 2005;Fulvio et al, 2012). In this paper we also consider the results obtained after pulsed laser irradiation of silicate samples (Brunetto et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Recent observations by the Dawn mission confirmed the mineralogical connection between Vesta, HEDs, and V-type asteroids De Sanctis et al, 2012 and confirmed a highly impacted surface with two large, overlapping basins near the south pole, with the youngest one perhaps just $1 Gy old (Marchi et al, 2012b;Schenk et al, 2012). However, laboratory studies suggest that ion irradiation on HEDs darkens and reddens the samples rapidly, corresponding to a space weathering timescale of 10 5 -10 6 years (Fulvio et al, 2012). The lack of space weathering on Vesta itself is thus a mystery (see summary by Pieters et al, 2006).…”
Section: Space Weatheringmentioning
confidence: 99%